Immunocytochemical detection of rhamnogalacturonan II on forming cell plates in cultured tobacco cells. Issue 5 (4th May 2017) - Zhou, Ye; Awano, Tatsuya; Kobayashi, Masaru; Matoh, Toru; Takabe, Keiji
Abstract: Rhamnogalacturonan II (RG-II) is a region of pectin macromolecules that is present in plant primary cell walls. The RG-II region serves as the site of borate cross-linking within pectin, via which pectin macromolecules link together to form a gel. In this study, we examined whether RG-II is present in the cell plate, the precursor of primary cell walls that forms during cytokinesis. A structure inside dividing cells was labeled with a rabbit polyclonal anti-RG-II antibody and detected by immunofluorescence microscopy. An antibody against callose, a marker polysaccharide for the cell plate, also labeled the structure. In immunoelectron microscopy analyses using the anti-RG-II antibody, gold particles were distributed in electron-lucent vesicular structures that appeared to correspond to the forming cell plates in late anaphase cells. Together, these results suggest that RG-II is present in cell plates from the early phase of their assembly. Abstract : :